Co-occurrence of periodontal lesions and dental wear in incisor and masticatory teeth in two sheep flocks in Brazil - Agostinho, Sabrina Donatoni [UNESP]; Borsanelli, Ana Carolina; Campello, Paula Letícia [UNESP]; Saraiva, Júlia Rebecca [UNESP]; Silva, Tamires Ataides; Schweitzer, Christiane Marie [UNESP]; Gaetti-Jardim, Elerson [UNESP]; Dutra, Iveraldo dos Santos [UNESP] (Wiley, 2024)
Background: Periodontitis and tooth wear are multifactorial diseases with distinct etiopathogenesis that affect the health, feed efficiency and welfare of sheep. Methods: This study evaluated the co-occurrence of tooth wear and periodontal lesions in 129 ewes from two Brazilian flocks, clinically classified the lesions and presence of dental calculus, and identified potential pathogens in the dental biofilm of 63 ewes by polymerase chain reaction. Results: Of the 129 ewes included in the study, 75 presented periodontal lesions, while all animals presented tooth wear and dental calculus. Of the animals with periodontal lesions, 16.2% had lesions in incisor teeth and 52.7% in masticatory teeth. Regarding excessive tooth wear, 38.6% had severe wear on the incisor teeth and 89.1% on the masticatory teeth. Ewes older than 36 months had a higher frequency of periodontal lesions in incisor teeth (p < 0.001) and a greater amount of dental calculus (p < 0.001), but there was no association between tooth wear and animal age. Fusobacterium nucleatum, Tannerella forsythia and Fusobacterium necrophorum predominated in periodontal lesions. Limitation: This study is limited by the small sample size and lack of diagnostic imaging to assess periodontal disease. Conclusion: The co-occurrence of periodontal lesions and excessive dental wear involving both the incisor and masticatory teeth suggests that although the two diseases have different aetiologies, they likely have common risk factors.
Keywords: broken mouth; dental calculus; gingival recession; periodontitis; sheep; tooth wear